Prioritising the solutions to overcome the barriers of green supply chain management implementation: a hybrid fuzzy AHP- VIKOR framework approach. Issue 4 (2nd October 2018) - Malviya, Rakesh Kumar; Kant, Ravi
ABSTRACT: The objective of this study is to identify the green supply chain management barriers (GSCMBs) and to prioritise the solutions to overcome the barriers of GSCM implementation. Through literature review and expert discussion, total 36 GSCMBs and 20 solutions were identified. The nationwide survey was conducted to rank the GSCMBs. Twenty-nine GSCMBs (Mean≥2.50) out of 36 GSCMBs were selected for analysis. This study proposes a framework based on hybrid fuzzy AHP – VIKOR. The proposed methodology is helpful to overcome these GSCMBs for the success of GSCM implementation. The results show that 'integrate the reverse material flow in SC' is the highest ranked solution which provides useful insights for managers to formulate plans for benchmarking and setting targets for GSCM implementation through phase wise organisational priority to overcome the GSCMBs. This study provides an efficient, effective, robust and organised way to overcome the challenges to enhance the competencies of GSCM implementation.